Implications of multilingualism on the linguistic reality in Algeria - djoudi, sayah (El Omda in Linguistics and Discourse Analysis, 2024)
Multilingualism is a widespread phenomenon that can hardly be absent from any society. It refers to the use of two or more different linguistic systems within the same community. Algeria is among those societies characterized by linguistic and cultural diversity, where we find two national languages, Arabic and Amazigh, in addition to a foreign language, French. This article sheds light on the phenomenon of multilingualism and its positive and negative impacts on the linguistic reality in Algeria. Accordingly, it is necessary to propose a set of solutions and recommendations that could serve as essential remedies to address the challenges of our multilingual context, as well as to reduce the negative effects of linguistic plurality in Algeria.